ENCEPHALOPATHY OF THE RHEUMATIC PATIENT - PELLON, R; GORTARI, ALFONSO DE; COSTERO, ISSAC CARLOS (INSTITUTO NACIONAL DE CARDIOLOGIA, CD. MEXICO, DF, MEX, 1947)
Summaries of other communications presented at the Second Inter-American Congress of Cardiology
AM HEART J
Keywords: ENCEPHALOPATHY, RHEUMATIC, PATIENT; CIENCIAS MEDICAS; PATOLOGIA; ENCEFALOPATIA